The place of scientific information in the promotional activities of the International Olive Council. Olive oil and health: consumers’ perception - Fernández M. (Present and future of the Mediterranean olive sector, 2013)
The characteristics of olive oil are the main factor associated with the quality of the product. The Mediterranean Diet, health and taste are the aspects with which olive oils are most closely identified. In the minds of consumers, olive oils are chiefly seen as being healthy, nutritional, natural and easy to digest. All these properties make it the ideal choice of fat, not just because of its myriad health-promoting benefits but also because of its organoleptic and culinary attributes. One of the key aims of the IOC is to assert the sound nutritional and dietary benefits of olive oil, which is a core element of the Mediterranean Diet. Collecting and disseminating scientific knowledge on the nutritional and health related advantages of olive oil is central to the task of informing consumers about this product and promoting its consumption. Olive oil is the chief source of fat in the Mediterranean diet. In recent years there has been a surge of interest in this dietary model, which has been “rediscovered” as a result of studies on disease prevention. The key to the biological potential, nutritional properties and organoleptic characteristics of olive oil lies in its composition, which is also central to understanding its functions. Being a natural fruit juice, it retains the taste, aroma, vitamins and properties of the olive. The component fatty acids of the triglycerides in olive oil differ to a certain extent according to variety and growing conditions. Monounsaturated oleic acid is clearly the predominant fatty acid, accounting for between 55 and 83 per cent. Coupled with the large amount of antioxidants it contains, this adequate degree of unsaturation is what gives olive oil its distinctive heat resistance and stability. The presence of minor components, particularly large amounts of antioxidants and vitamins (tocopherols, carotenoids and phenolics), lend it very important protective properties. Extensive research has produced new data on the metabolism, bioavailability and numerous biological effects of olive oil, as well as on its effects in preventing cell oxidation, protecting against free radical damage and in preventing cancer and ageing. On top of its sensory and gastronomic properties, olive oil has numerous medical benefits in disease prevention which are being constantly corroborated by science. As a consequence of this combination of factors, today’s ever better informed consumers view olive oil as a product that is unique, healthy and natural.
International Seminar: Present and Future of the Mediterranean Olive Sector, 2012/11/26-28, Zaragoza (Spain)